IDENTIFICATION OF SUBSURFACE SULFIDE ORE DEPOSITS USING GROUND MAGNETIC EXPLORATION TECHNIQUE: A CASE STUDY FROM DROSH-KALDAM GOL, CHITRAL, NORTHERN PAKISTAN - Azeem Khan,; Khaista Rehman,; Asghar Ali, (Spectrum of Engineering Sciences, 2025)
The ground magnetic data over parts of Gawuch Formation at Drosh-Kaldam Gol, Chitral region has been analyzed both qualitatively and quantitatively with the aim to map subsurface sulfide mineralization, analyze structural lineaments and their influence on mineralization, ascertain the depth of causative source bodies and pinpoint economically viable sulfide drilling prospects in the area. In the study area, the total magnetic intensity values range from a minimum of 48,500 nanoteslas (nT) to a maximum of 56,000 nT, whereas the residual magnetic anomaly levels span from -3000 nT to 4500 nT. The qualitative structural analysis of magnetic data using various visualizations have yielded detailed insights into the subsurface geological features and has successfully pinpointed and delineated numerous anomalous zones (A, B, C, D & E) having the potential for occurrence of sulfide ore minerals and are proposed as a promising drilling targets for sulfide mineral prospection in the area. The quantitative analysis using Peter’s half slope and Maximum slope technique indicatesthat the magnetic anomaly sources in the study area range from near-surface to around 22.37 meters deep, suggesting shallow mineralization targets. The magnetic data analysis also reveals a shallow and sporadic network of circular to semicircular NE-SW trending magnetic discontinuities/structural lineaments (faults/fractures) which facilitate the process of hydrothermal mobilization and exert a significant impact on the spatial distribution of sulfide mineralization, which is associated with diorite-granodiorite intrusions and displays characteristics typical of porphyry systems. The findings demonstrated that magnetic method is a dependable tool for mapping subsurface structures, which are essential for evaluating the potential of sulfide ore minerals in complex topographic and geological settings.